Experimental study of micro-explosion and puffing of gas-to-liquid (GTL) fuel blends by suspended droplet method - Rosli, M.A.F. (Elsevier Ltd, 2021)
In this study, a set of GTLâdiesel fuel blends (G20, G50, G80, and G100, where the number represents the percentage of GTL fuel in the fuel blend) are prepared. Subsequently, using the suspended droplet method in a controlled heating chamber, the evaporation behaviour of these GTL fuel blends is visualised using a high-speed camera connected to a long-distance microscope. It is found that, among the tested fuel blends, puffing is not observable for G100, whereas micro-explosions are absent for G20. In comparison, the remaining fuel blends experience both these phenomena. In addition, the highest enlargement factor is observed for G20, followed by G50 and G80, whereas G50 has the highest micro-explosion intensity, followed by G80 and G100. Finally, the numbers and sizes of the child droplets are determined by adjusting the detection threshold, and it is found that G50 has the highest number of child droplets, followed by G80, G100, and G20. The results indicate that the presence of 50 GTL fuel in a GTLâdiesel fuel blend (by volume) can lead to the best droplet micro explosions compared to the rest of the tested fuel blends. Â© 2020 Elsevier Ltd